Time course of ischemic and bleeding burden in consecutive patients undergoing transcatheter aortic valve replacement (FOCUS-ONE Registry). (15th June 2023) - Esposito, G.; Montalto, C.; Crimi, G.; Grippo, R.; Morici, N.; Bruschi, G.; Testa, L.; De Marco, F.; Soriano, F.; Nava, S.; Stefanini, G.; Bedogni, F.; et al.
Abstract: Background and aims: Ischemic or bleeding events might occur after transcatheter aortic valve replacement (TAVR), with the potential to hamper clinical outcomes. This study aimed to characterize the average daily ischemic risks (ADIRs) and the average daily bleeding risks (ADBRs) over 1-year in all consecutive patients undergoing TAVR. Methods: ADBR included all bleeding events according to VARC-2 definition, and ADIR included cardiovascular deaths, myocardial infarction and ischemic stroke. ADIRs and ADBRs were assessed within different timeframes post TAVR: acute (0–30 days), late (31–180 days), and very late (>181 days). Generalized estimating equations were used to test the least squares mean differences for the pairwise comparison of ADIRs and ADBRs. Our analysis was performed in the overall cohort and according to antithrombotic strategy (LT-OAC vs No LT-OAC). Results: Ischemic burden was higher than bleeding burden, independently from the indication to LT-OAC, and in all timeframes examined. In the overall population, ADIRs were three-fold ADBRs (0.0467 [95% CI, 0.0431–0.0506] vs 0.0179 [95% CI, 0.0174–0.0185]; p < 0.001*). While ADIR was significantly higher in the acute phase, ADBR was relatively stable in all timeframes analysed. Of note, in LT-OAC population, OAC + SAPT group showed lower ischemic risk and higher bleeding events compared with OAC alone (ADIR: 0.0447 [95% CI: 0.0417–0.0477] vs 0.0642 [95% CI: 0.0557–0.0728]; p < 0.001*, ADBR 0.0395 [95% CI: 0.0381–0.0409] vs 0.0147 [95% CI: 0.0138–0.0156]; p < 0.001*). Conclusions: In patients undergoing TAVR Average daily risk fluctuates over time. However, ADIRs overcome ADBRs in all timeframes, especially in the acute phase and regardless of antithrombotic strategy adopted. Graphical abstract: ADR - average daily risk; ADIR - average daily ischemic risk; ADBR - average daily bleeding risk; LSMD - least mean square difference Unlabelled Image Highlights: This study shows the great variability between ADIR and ADBR in the first 30 days after TAVR, with the highest prevalence of ischemic risk. ADIR overcome ADBR in all timeframes with greater differences in the acute phase, which might be related to the procedural ischemic factors. Understanding the time-dependent trend of ADR, highlights how an oversimplified approach, might be inadequate to capture the complexity of the phenomenon. Bearing this in mind, a tailored antithrombotic strategy could improve clinical outcomes as a result of a balance between ischemic and bleeding risk.